Ultrasonographic approach for a foot ganglion after sewing masks in the COVID-19 pandemic: Blessing in disguise - Hrehová, Laura; Mezian, Kamal; Özçakar, Levent (Work, 2020)
BACKGROUND: During the coronavirus disease (COVID-19) pandemic, people volunteered for sewing hand-made face masks. However, sewing-machine operating might be associated with high ergonomic risk and a negative impact on musculoskeletal health. OBJECTIVE AND METHODS: This paper describes an ultrasonographic diagnosis of a foot ganglion - after sewing 300 face masks within two months using a foot-operated sewing machine. RESULTS: The patient significantly improved after an ultrasound-guided aspiration and corticosteroid injection. CONCLUSION: In short, we highlight the importance of ultrasound examination in the management of work (overuse)-related disorders in occupational medicine practice.
Keywords: anestetika lokální; trimekain; antiflogistika; poranění z opakovaného přetěžování; nemoci nohy (od hlezna dolů); Female; SARS-CoV-2; Ganglion Cysts; Anesthetics, Local; Methylprednisolone Acetate; ženské pohlaví; Volunteers; Foot Injuries; textilní průmysl; lidé; methylprednisolon acetát; Foot Diseases; dobrovolní pracovníci; cystická ganglia; drenáž; COVID-19; Drainage; Trimecaine; masky; pandemie; intervenční ultrasonografie; Ultrasonography, Interventional; nemoci z povolání; Textile Industry; Cumulative Trauma Disorders; Anti-Inflammatory Agents; Occupational Diseases; lidé středního věku; poranění nohy (od hlezna dolů); Pandemics; Middle Aged; Masks; Humans